Analisis Pengaruh Jumlah Responden pada Evaluasi Usabilitas Aplikasi Edukasi Anak-Anak - Melita Puspitasari; Rini Dharmastiti (Forum Teknik, 2015)
The development in technology for children is now increasing. In order to make the design and appearance of a software/application is easy to operate, run, and understood by children, an usability test is needed. One method that popular in usability testing is thinking aloud that takes at least 3-5 samples so the optimal problem can be found during test. This study aims to determine whether the needs of the number of respondents in the thinking aloud method is still relevant today, especially when applied to children, and to determine the effect of number of children involved in the test on usability problems found.This study involved 10 children assubjects with a mean age of 10,6 years to play educational application that run on Apple Ipad 2 named Candy Factory. However, the number of respondents in usability test on children's educational application has the effect that the more the number of respondents, the more problems found but only up to 4 respondents. More than 4 respondents, the usability problems that found is decreasing because the children keep revealing the same problem. One respondentwas able to found 45,45% usability problems, and 85% usability problems found by only 4 respondents. While 100 % usability problems can be found by 9 respondents. Moreover, the result of usability test analysis and recommendations for improvement of Candy Factory are explained.Keywords: usability, number of respondent, thinking aloud, educational game, children